FORMATION AND USE OF BUDGETS OF TERRITORIAL SOCIETIES (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Abstract. Introduction. In the article the features of financial decentralization of local authorities are described in Ukraine. It is marked that a local budget plays an important role effective socio-economic development of territorial society. The features of forming and use of money of local budgets of territorial communities are certain in the conditions of financial decentralization. The sources of forming of profits of local budget are considered and on what use these money. Certainly, what part is occupied by a local budget in the Erected budget of Ukraine. Drawn conclusion, that in the conditions of financial decentralization, one of important questions for today is a construction of optimal model of forming and use of money of organs of local self-government and directions of improvement of the system of the financial providing of local self-government of territorial are offered.The purpose of the article. The purpose of the article consists in deepening of theoretical ground of essence of local budget and search of sourcings of the local programs for providing of socio-economic development of territory.   Results. In the article the features of financial decentralization of local authorities are described in Ukraine. Reform of decentralization in Ukraine substantially influenced on the process of forming and use of money of local budgets. A local budget presents by a soba powerful lever of management that gives an opportunity to the organs of local self-government to influence on economic, social and political processes in society. On the basis of analysis of scientific literature it was set about absence of only approach of scientists in relation to understanding of essence of concept "local budget". It is considered, from what the profits of local budget are formed and on what use these money. Tax receivabless, untax receivabless, income from operations with a capital and interbudgetary трансферти, belong to the basic sources of forming of profitable part of territorial communities. By the basic source of filling of budget money are tax receivabless. Unlike profits, the charges of budget in swingeing majority potentially can be attributed to the budgetary stimuli. Certainly, that reform of decentralization substantially influenced on profitable part of local budgets. For the last three years the profits of local budgets of Ukraine grew considerably. However, simultaneously financing of greater part of charges, territorial communities related to life, now comes true due to their budgets.Conclusiоns. Financial decentralization has positive influence on providing of communities and possibility financial resources them the effective use. However the real state of the financial providing of organs of local self-government on implementation of own and delegated by a central government of plenary powers body is extraordinarily difficult. The analysis of data confirms, about dependence of organs of local self-government on national tax payments and interbudgetary трансфертів that is actually unconnected with own activity of territorial communities. To Tom, one of important questions for today are reduction to the role of the state in the financial providing of development of communities and construction of optimal model of forming and use of money of organs of local self-government. In the article by us directions of improvement of the system of the financial providing of local self-government of territorial were offered
Keywords: local budget, territorial society, financial decentralization, profits of local budgets, charges of local budgets.